Assessment of the Impact of the 2003 and 2006 Heat Waves on Cattle Mortality in France - Morignat, Eric; Perrin, Jean-Baptiste; Gay, Emilie; Vinard, Jean-Luc; Calavas, Didier; Hénaux, Viviane (PLOS ONE, 2014)
Objectives While several studies have highlighted and quantified human mortality during the major heat waves that struck Western Europe in 2003 and 2006, the impact on farm animals has been overlooked. The aim of this study was to assess the effect of these two events on cattle mortality in France, one of the most severely impacted countries. Methods Poisson regressions were used to model the national baseline for cattle mortality between 2004 and 2005 and predict the weekly number of expected deaths in 2003 and 2006 for the whole cattle population and by subpopulation based on age and type of production. Observed and estimated values were compared to identify and quantify excess mortality. The same approach was used at a departmental scale (a French department being an administrative and territorial division) to assess the spatio-temporal evolution of the mortality pattern. Results Overall, the models estimated relative excess mortality of 24% [95% confidence interval: 22–25%] for the two-week heat wave of 2003, and 12% [11–14%] for the three-week heat wave of 2006. In 2003, most cattle subpopulations were impacted during the heat wave and some in the following weeks too. In 2006, cattle subpopulations were impacted for a limited time only, with no excess mortality at the beginning or after the heat wave. No marked differences in cattle mortality were found among the different subpopulations by age and type of production. The implications of these results for risk prevention are discussed.